Workshop on drug screening & pharmacological evaluations / Assoc. Prof. Dr. Hanish Singh Jayasingh Chellammal ... [et al.] - Jayasingh Chellammal, Hanish Singh; Hasan, Mizaton Hazizul; Subramaniam, Vellayan; Jahidin, Aisyah Hasyila; Mahamood, Maziana; Zulkifli, Muhammad Harith; Latifi, Nur Sakinah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On 12th and 13th September 2023, Faculty of Pharmacy, UiTM, hosted a two-day program titled “Workshop on Drug Screening & Pharmacological Evaluations". This workshop is intended to educate researchers on how to conduct pharmacological and toxicological evaluations for drug development. The program was attended by UiTM students as well as external participants with medical, biomedical, pharmacy, and dental backgrounds. The workshop covered the basics of drug development beginning with preliminary toxicological evaluations of a new drug or chemical entity. Five lecture sessions were conducted covering the various aspects of drug discovery and evaluation such as the development of lead molecule, steps involved in the optimization of lead molecule, target-based drug discovery, physiology-based drug discovery, and general steps of various in-silico techniques. The lecture series also encompassed basic guidelines on Organization for Economic Co-operation and Development (OECD) and drug testing in preclinical stages.